89 Human factors training can have an immediate impact on trainee behaviours. (17th November 2016) - Bamford, Richard; Humphreys, A; Burnand, H; Longman, R; Acharya, M; Coulston, JE
Abstract : Introduction: Training courses related to Human Factors aim to give participants the skills and strategies to understand and manage challenging situations and complex professional relationships in the workplace. However, identifying whether this is achieved can be challenging. We aim to assess whether trainees attending a Human Factors Course adopt these strategies. Method: Trainees who attended a Surgical Human Factors Training Day at the Bristol Medical Simulation Centre were recorded whilst participating in four different scenarios that reflected challenging and realistic clinical events. Three independent assessors reviewed the video and scored the group in the areas of leadership, teamwork, situational awareness, decision-making and communication on a 1–5 scale based upon OSAT algorithm. The collated scores were assessed and differences in behaviour amongst the groups throughout the day were analysed. Results: Two courses and 32 trainees were recorded. 18/32 were core trainees and 14/32 were specialist trainees in orthopaedics and general surgery. 9/32 (28%) had attended Human Factors courses previously. Scores of each area identified significant improvements in teamwork (p = 0.001), leadership (p = 0.02), situational awareness (p = 0.04), decision-making (p < 0.05) and communication (p = 0.001). Higher surgical trainees taking part in the day appeared to change behaviour at a faster rate from the core trainees. Conclusion: Human factors courses can significantly modify and improve a trainees behaviour during training. Further research is required to identify whether this modification is sustainable and transferable to clinical practice.